Negative association between left prefrontal GABA concentration and BDNF serum concentration in young adults. Issue 5 (May 2020) - Müller, Sabrina Theresia; Buchmann, Andreas; Haynes, Melanie; Ghisleni, Carmen; Ritter, Christopher; Tuura, Ruth; Hasler, Gregor
Abstract: Background: The brain's major inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and the brain-derived neurotrophic factor (BDNF) play important roles in several stress-related disorders. Magnetic resonance spectroscopy (MRS) allows for non-invasive quantification of GABA concentration in the brain. We investigated the relationship between GABA concentration in the left dorsolateral prefrontal cortex (DLPFC) and BDNF concentration in the serum in a community-based sample of young subjects. Methods: For the GABA measurement a single voxel MR spectrum was assessed in the prefrontal lobe (25 × 40 × 30 mm) using the MEGA-PRESS method in 276 subjects. BDNF serum concentrations were assessed with an ELISA kit. For 147 subjects we had both MRS and BDNF serum data, and for 79 subjects we had genotype data on the BDNF rs6265 polymorphism. Depressive psychopathology was assessed using Beck's Depression Inventory (BDI), Montgomery-Asberg Depression Rating Scale (MADRS) and Structured Clinical Interviews for Diagnostic and Statistical Manual of Mental Disorders (SCID) for DSM-IV. Results: GABA concentration in the left DLPFC was negatively associated with BDNF serum concentration (r = -.264, p = .001). This correlation remained significant if corrected for sex (r = -.264, p = .001). BDNF serum concentration was also positively associated with volumes and surface areas of the left prefrontal cortex (p = .048, p = .005). There were no significant associations or interaction with depressive psychopathology (BDI, MADRS, SCID) or rs6265. Conclusion: The results of this study suggest that GABA, BDNF and prefrontal brain volumes are interrelated, but do not show a strong association to depressive psychopathology, possibly due to the mild forms of psychiatric conditions present in our community-based sample. Abstract : Neuroscience; Human Genetics; Psychiatry; Depression; Psychopharmacology; Clinical Psychology; BDNF; GABA; MRS; Neuroimaging; Stress